Inmates' Self-Reported Physical and Mental Health Problems: A Comparison by Sex and Age. (October 2020) - Lane, Charlene; Bratina, Michele P.; Antonio, Michael E.
The present study explored the impact of both age and sex on inmates' self-reported physical and mental health problems. The inmates were older adults (55 or older) and housed in one of four correctional institutions from a state located in the northeastern region of the United States. Overall, findings revealed female inmates more often reported currently taking prescribed medications for mental or emotional problems and previously having been diagnosed with mental health problems prior to incarceration. Also, comparing male and female inmates by age categories (59 and younger vs. 60 and older), the older group was more likely to report a variety of physical problems including arthritis, diabetes, and glaucoma. Research and correctional policy implications are discussed.